Characterization of the Mycobiome of the Seagrass, Zostera marina, Reveals Putative Associations With Marine Chytrids - Ettinger, Cassandra L.; Eisen, Jonathan A. (Frontiers in Microbiology, 2019)
Seagrasses are globally distributed marine flowering plants that are foundation species in coastal ecosystems. Seagrass beds play essential roles as habitats and hatcheries, in nutrient cycling and in protecting the coastline from erosion. Although many studies have focused on seagrass ecology, only a limited number have investigated their associated fungi. In terrestrial systems, fungi can have beneficial and detrimental effects on plant fitness. However, not much is known about marine fungi and even less is known about seagrass associated fungi. Here we used culture-independent sequencing of the ribosomal internal transcribed spacer (ITS) region to characterize the taxonomic diversity of fungi associated with the seagrass, Zostera marina. We sampled from two Z. marina beds in Bodega Bay over three time points to investigate fungal diversity within and between plants. Our results indicate that there are many fungal taxa for which a taxonomic assignment cannot be made living on and inside Z. marina leaves, roots and rhizomes and that these plant tissues harbor distinct fungal communities. We also identified differences in the abundances of the orders, Glomerellales, Agaricales and Malasseziales, between seagrass tissues. The most prevalent ITS amplicon sequence variants (ASVs) associated with Z. marina tissues could not initially be confidently assigned to a fungal phylum, but shared significant sequence similarity with Chytridiomycota and Aphelidomycota. To obtain a more definitive taxonomic classification of the most abundant ASV associated with Z. marina leaves, we used PCR with one primer targeting a unique region of this ASVs ITS2 and a second primer targeting fungal 28S rRNA genes to amplify part of the 28S rRNA gene region corresponding to this ASV. Sequencing and phylogenetic analysis of the resulting partial 28S rRNA gene revealed that the organism that this ASV comes from is a member of Novel Clade SW-I in the order Lobulomycetales in the phylum Chytridiomycota. This clade includes known parasites of freshwater diatoms and algae and it is possible this chytrid is directly infecting Z. marina leaf tissues. This work highlights a need for further studies focusing on marine fungi and the potential importance of these understudied communities to the larger seagrass ecosystem.